Nurses reports of actual work hours and preferred work hours per shift among frontline nurses during coronavirus disease 2019 (COVID-19) epidemic: A cross-sectional survey - Xia Zhang; Zhixia Jiang; Xiaoli Yuan; Ying Wang; Di Huang; Rujun Hu; Jiamei Zhou; Fang Chen (Elsevier, 2021)
Background: The Coronavirus disease (COVID-19) pandemic is an ongoing pandemic all over the world, leading to 126, 372, 442 people diagnosed and 2, 769, 696 deaths globally as of March 28, 2021. Nurses are providing care to patients with COVID-19 who require hospitalization. To ensure adequate response capacity and to maintain the health of nurses, it is important to analyse the actual work hours and the nurses reported preferred work hours per shift among frontline nurses. Objective: To analyse the actual work hours and preferred work hours per shift of nurses reports among frontline nurses fighting the COVID-19 epidemic and to explore the influencing factors on the nurses reported preferred work hours. Design: Cross-sectional survey Setting(s): This study was conducted in 10 designated hospitals providing treatments to patients with COVID-19 in China. Participants: Nurses providing care to patients with COVID-19 in designated hospitals in China. Methods: A questionnaire with open-ended questions was used to assess frontline nurses caring for COVID-19 cases in 10 designated hospitals. Quantitative and qualitative methods were used to analyse the actual work hours, the nurses reported preferred work hours and factors influencing nurses reported preferred work hours among the frontline nurses. Results: A total of 109 nurses responded to the survey. The shift length exceeded the nurses' preferred work hours [Median (interquartile range): 5.00 (2.00) h vs 4.00 (2.00) h; Minimum-Maximum: 4-12 h vs 4-8 h], and 60.55% (66/109) of the nurses regarded 4 h as the preferred number of work hours per shift. Five key themes associated with the influencing factors emerged, including circumstances; personal preventable equipment; the nurses' physical and emotional needs of nurse; and the nurses' safety needs and work intensity. Conclusions: These findings suggest that there is a gap between the actual work hours and the nurses preferred work hours among frontline nurses in different units and different posts. The main influencing factors were circumstances, personal protective equipment, the nurses' physical and emotional needs, and the nurses' safety needs and work intensity.